Biodegradable, Recyclable, and Renewable Polymers as Alternatives to Traditional Petroleum-based Plastics - Samuel, Humphrey Sam; Ekpan, Francis-Dominic Makong; Ori, Merit Oluchi (Asian Journal of Environmental Research, 2024)
The environmental impact of conventional plastics has spurred the development of biodegradable, recyclable, and renewable polymers as sustainable alternatives. Biodegradable, recyclable, and renewable polymers are developing as viable alternatives to standard petroleum-based plastics due to their environmental benefits and sustainability. These polymers can be manufactured using renewable sources such as plants and microbes, reducing reliance on fossil fuels and minimizing plastic pollution. Biodegradable polymers offer end-of-life solutions through composting or natural breakdown, reducing plastic pollution. Recyclable biopolymers can be processed into new products, minimizing waste. Renewably sourced polymers utilize biomass, a natural resource, to lessen dependence on fossil fuels. These polymers, derived from renewable resources such as plant-based materials, agricultural by-products, and microbial fermentation, offer several advantages over conventional plastics, including reduced environmental impact, decreased dependence on fossil fuels, and enhanced end-of-life options.